The Effect of the Use of Multimedia Flip Book With the Flipped Classroom Approach in Vocational Schools - Oktarina, Rahmi; -, Ambiyar; -, M.Giatman; -, Fadhilah; Muskhir, Mukhlidi; Effendi, Hansi (Journal of Education Technology, 2021)
The problem encountered in learning operating system teaching materials majoring in network computer engineering is the lack of creativity in students' thinking skills so that they experience obstacles in the practical process. This study used a quasi-experimental design with a pretest-posttest Control Group Design. Data collection techniques using tests. The pre-test was carried out at the beginning to see the students' initial abilities before being given treatment, the post-test was carried out to test the effectiveness or compliance of the application of the treatment. In this study, the data analysis technique used 3 statistical tests, (1) normality test, (2) homogeneity test and (3) hypothesis testing. Through the use of hypothesis testing to show the results of H0 is rejected and H1 is accepted with a significance level of 5% so that the value is (P <0.05). The conclusion is that the use of the Flip book Multimedia with the Flipped Classroom approach is able to improve the thinking skills of students majoring in network computer engineering in the operating system subject. So that later research can be applied to other subjects to help the learning process and increase the creativity of vocational high school studentsÂ